(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
A yurt is a portable frame dwelling with a felt covering among the Turkic and Mongol-speaking peoples. Perhaps the prototype of the yurt in the Late Bronze Age of the 12th-9th centuries BC were the dwellings of the Andronovo people. In the middle of the 1st millennium in Central Asia, great changes occurred in the basis of the yurt. The yurt fully satisfies the needs of a nomad due to its convenience and practicality. It is quickly assembled and easily disassembled by one family within one hour. It is easily transported by camels, horses or cars; its felt covering does not allow rain, wind and cold to pass through. The hole at the top of the dome provides daylight and allows the use of the fireplace. Kazakh yurts are lower than Kyrgyz ones due to strong winds in the steppe. Mongolian, Buryat and Tuvan yurts are even lower due to straight ceiling poles.The Kyrgyzes yurt usually faces east. The right side (when viewed from the outside) of the entrance is female (epchi jak) with household utensils, the left is male (er zhak) for a gun, bridle, saddle, etc., opposite the entrance is a place of honor (tөр/tör), the center of the yurt is place for a hearth.